Peaks and Plains of Central Asia - Schomberg, R. C. F., Col. (Lahore Sang-e-Meel Publications, 1996)
Include Illustrations, Maps, Glossary and Index.
Keywords: Travel -- China--Xinjiang Uygur Zizhiqu -- Schomberg, R. C. F. (Reginald Charles Francis), 1880-1958